'Head held high and carrying on': Reflections from GPNs on the impact of COVID-19. (2nd December 2020) - Henry, Heather
Abstract : Twitter is a useful tool for nurses to use to share experiences and network, particularly while opportunities to meet face-to-face are reduced. Heather Henry gives an overview of a tweet chat on how COVID-19 has affected nurses working in general practice